THE RATIONALE FOR CALCULATING THE RATE OF DISCOUNTING INVESTMENT PROJECTS OF UZ - Sherepa, O. M. (Science and Transport Progress, 2006)
The article substantiates the calculus of the discount rate for increasing efficiency of Ukrzalizniza’s investment projects.